Polysaccharides extracted from tucum-do-cerrado fruits (Bactris setosa Mart) have antineoplastic effects in mice while preserving hepatic gluconeogenesis - de Oliveira, Kauê Marcel; Abboud, Kahlile Youseff; Radulski, Débora Rasec; Faria, Bruna Christ; Galindo, Claudia Martins; Pereira, Gabriela Saidel; Stipp, Maria Carolina; Corso, Claudia Rita; de Assis, Camila Bach; de Lima Martins, Juliana Nunes; do Amaral, Luane Aparecida; Comar, Jurandir Fernando; et al. (International journal of biological macromolecules, 2024)
This study investigated the antitumoral, anti-inflammatory and oxidative effects of polysaccharides from tucum (Bactris setosa, TUC) using the Ehrlich carcinoma as a tumor model. Additionally, the glycogen content, cytochrome P levels, and gluconeogenesis from lactate were assessed in the liver of healthy animals. Tumor-bearing female mice were orally treated with 50 and 100 mg.kg−1 of TUC or vehicle, once a day, or with 1.5 mg.kg−1 methotrexate via i.p., every 3 days, along 21 days. Both doses of TUC reduced the tumor weight and volume. In the tumor tissue, it decreased GSH and IL-1β levels, and increased LPO, NAG, NO and TNF-α levels. The tumor histology showed necrosis and leukocytes infiltration. The metabolic effects of TUC were investigated by measurement of total cytochrome P (CYP) and glycogen in tumor-bearing mice, and by ex vivo liver perfusion on non-bearing tumor male mice, using lactate as gluconeogenic precursor. Metabolically, the hepatic glucose and pyruvate productions, oxygen uptake, and the total CYP concentration were not modified by TUC. Thus, tucum-do-cerrado polysaccharides have antitumor effects through the modulation of oxidative stress and inflammation, without impairing glucose production from lactate in the liver, the main organ responsible for the metabolism of organic and xenobiotic compounds. [Display omitted] •Polysaccharides from the fruit of the tucum-do-cerrado (TUC) are composed mainly of glucomannan and glucuronoarabinoxylan.•TUC have antitumor effects against the Ehrlich mammary tumor model in mice.•TUC treatment modulates oxidative stress and the inflammatory response in the tumor microenvironment.•TUC treatment induces necrosis in mammary tumor tissue.•TUC does not modify hepatic gluconeogenesis from lactate when perfused directly into the isolated liver of mice.